Audio Visual dan Power Point sebagai Media Edukasi dalam Merubah Pengetahuan dan Perilaku Remaja - Netti Herawati; Pauline Kusmaryati; Ajeng Galuh Wuryandari (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effect of health education on personal hygiene with audio-visual media (video) on the knowledge and behavior of adolescent girls. This quantitative research method uses a pretest-posttest design with a control group design with the type of intervention using video learning in the intervention group. The results of the t-test showed that the knowledge aspect was p-value = 0.587 (p > 0.05), while the behavior was 0.011 (sig < 0.05). In conclusion, health education using audio-visual (video) is proven to improve the behavior of adolescent girls in improving personal hygiene and is more effective than learning using PPT. Keywords: Menstruation, Knowledge, Behavior, Personal Hygiene